PtdIns3P phosphatases MTMR3 and MTMR4 negatively regulate innate immune responses to DNA through modulating STING trafficking - Dewi Pamungkas Putri, Dyaningtyas (J Biol Chem, 2019)
The innate immune system plays an essential role in initial recognition of pathogen infection by producing inflammatory cytokines and type I interferons. cGAS is a cytoplasmic sensor for DNA derived from DNA viruses. cGAS binding with DNA induces the production of cGAMP, a second messenger that associates with STING in endoplasmic reticulum (ER). STING changes its cellular distribution from ER to perinuclear Golgi, where it activates the protein kinase TBK1 that catalyzes the phosphorylation of IRF3. Here we found that STING trafficking is regulated by myotubularin-related protein (MTMR) 3 and MTMR4, members of protein tyrosine phosphatases that dephosphorylate 3′ position in phosphatidylinositol (PtdIns) and generate PtdIns5P from PtdIns3,5P(2) and PtdIns from PtdIns3P. We established MTMR3 and MTMR4 double knockout (DKO) RAW264.7 macrophage cells and found that they exhibited increased type I interferon production after interferon-stimulatory DNA (ISD) stimulation and herpes simplex virus 1 infection concomitant with enhanced IRF3 phosphorylation. In DKO cells, STING rapidly trafficked from ER to Golgi after ISD stimulation. Notably, DKO cells exhibited enlarged cytosolic puncta positive for PtdIns3P and STING was aberrantly accumulated in this puncta. Taken together, these results suggest that MTMR3 and MTMR4 regulate the production of PtdIns3P, which plays a critical role in suppressing DNA-mediated innate immune responses via modulating STING trafficking.